Avaliação da eficiência de lagoas de estabilização no tratamento de resíduos esgotados de fossas sépticas - Medeiros, Daniel Dantas Viana (2009)
Because of disability in public policy development in mind to attend issues of sanitation in the municipalities, companies known as "clean-blue" appeared proposing to solve a simple collection and management of wastewater produced in single or multifamily residences, commercial, hospitals, etc. In the case of an activity in which there are no worries about the fate of sewage, emerged some doubts about the degree of health and environmental safety in these companies. Traditionally, most of them makes the provision of waste depleted soil or wetland, open, usually located on the outskirts of cities (MENESES, 2001). In turn, the sludge from septic tanks exhausted, provided no technical criteria - in the soil, rivers and as an agricultural fertilizer put in risk the health of the population and environmental quality. This work was entered in the search network 5 of the Notice of the Research Program in Sanitation - PROSAB-5, aimed to study the theme 'Characterization and study of alternative ways of treating sludge from septic tanks in the city of Natal, RN', proposing to evaluate the performance of the use of stabilization ponds as a system to handle waste from septic tanks exhausted. A series of lakes studied belong to one of the largest clean-pit of Natal, consisting of two anaerobic ponds, one facultative and maturation, and a tank disinfection, the wastewater being released in the Potengi River. Samples were collected between the months of October 2007 to October 2008, at six points previously defined and judged as more appropriate to what is proposed study. The analysis results in field and laboratory showed the most significant removal of COD (88.93%), total suspended solids (94.87%), organic nitrogen (66.87%) and thermotolerant coliforms (99.88%). Some results have not reached the expected because the system under study had operating problems that have undermined the efficiency of the reactors